Technical results, clinical efficacy and predictors of outcome of intercostal arteries embolization for hemothorax: a two-institutions’ experience - Tamburini, Nicola; Carriel, Nicole; Cavallesco, Giorgio; Molins, Laureano; Galeotti, Roberto; Guzmán, Rudith; Salviato, Elisabetta; Sánchez-Lorente, David; Maietti, Elisa; Maniscalco, Pio; Boada, Marc (Journal of Thoracic Disease, 2019)
Background: To evaluate the clinical efficacy and identify the predictors of outcome of intercostal arterial embolization for hemothorax caused by intercostal artery (ICA) injuries. Methods: A retrospective multi-institutional study was conducted. Outcomes were analyzed in 30 consecutive patients presenting with hemothorax caused by active ICA hemorrhage undergoing transcatheter arterial embolization (TAE). Clinical and procedural parameters were compared between outcomes groups. Results: Overall technical success rate was 87% (n=26). Among the 4 failed cases, 2 underwent repeated TAE and 2 underwent additional surgery. Overall 30-day mortality rate was 23%. Low haemoglobin levels and haematocrit, hepatic comorbidities and more than one artery undergoing embolization increased technical failure rate significantly. Survival was poorer in patients with massive bleeding. Conclusions: ICA embolization was found to be a safe and effective method in treating hemothorax caused by active ICA haemorrhage. Careful pre-embolization evaluation may be required for patient with low haemoglobin levels and haematocrit, hepatic comorbidities and active haemorrhage from more than one artery.